Yemeni opposition to Ottoman rule: an overview - Yaccob, Abd Rauh (Proceedings of the Seminar for Arabian Studies, 2012)
Most of the history of the Ottomans in Yemen is marked by a series of uprisings of Yemenis against the Ottoman presence. This paper attempts to trace the general pattern of opposition to Ottoman rule in Yemen before the conclusion of the Treaty of Da˓ān in 1911. Relations between Yemenis and Ottomans were hostile for a number of reasons, notably the malpractices of Ottoman officials. This was further stimulated by the Zaydī political concept which encouraged them to rise up against any unjust ruler in the name of religious duty. Their imām thus gained support and approval from Zaydī tribesmen and notables. The paper will also examine the content of the Treaty of Da˓ān; the aim of the uprising was finally achieved through this treaty, which not only benefited the imām and the Zaydīs but also the Ottomans.